The joint Simon effect: a review and theoretical integration - Dolk, Thomas; Hommel, Bernhard; Colzato, Lorenza S.; Schütz-Bosbach, Simone; Prinz, Wolfgang; Liepelt, Roman (Frontiers in Psychology, 2014)
The social or joint Simon effect has been developed to investigate how and to what extent people mentally represent their own and other persons’ action/task and how these cognitive representations influence an individual’s own behavior when interacting with another person. Here, we provide a review of the available evidence and theoretical frameworks. Based on this review, we suggest a comprehensive theory that integrates aspects of earlier approaches–the Referential Coding Account. This account provides an alternative to the social interpretation of the (joint) go-nogo Simon effect (aka the social Simon effect) and is able to integrate seemingly opposite findings on joint action.